Analisis Implementasi Prinsip Evaluasi Pembelajaran Di Sdn 060970 Bagan Deli - Situmorang, Patresia; Br Siregar, Permata Sari; Silalahi, Riris; Syahrial, Syahrial (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2024)
The background of this research is that the evaluation of learning outcomes carried out in the 2013 Curriculum-based learning process often does not comply with the standards for assessing the results of the 2013 Curriculum learning evaluation. The aim of this research is to describe and analyze the implementation of learning evaluation principles at SDN 060970 Bagan Deli , Medan Belawan City. This research use desciptive qualitative approach. Data collection techniques used observation sheets and interview sheets for management of 2013 curriculum learning evaluations. The population of this study were all homeroom teachers who taught using the 2013 curriculum at SDN 060970 Bagan Deli. The results of research conducted by researchers at SD Negeri 060970 Bagan Deli, Medan, Belawan City for the homeroom teachers of classes III, V and VI, there were 3 problems experienced by teachers in implementing learning outcomes evaluation in the 2013 Curriculum, including that the assessment of learning outcomes was not in accordance with assessment standards. 2013 Curriculum. The main aspects of the 2013 Curriculum are Graduate Competency Standards (SKL), Core Competencies (KI), Basic Competencies (KD), and Scientific Approach and Authentic Assessment-based indicators.